Hospital Nurses' Work Environment Characteristics and Patient Safety Outcomes: A Literature Review. (January 2018) - Lee, Seung Eun; Scott, Linda D.
This integrative literature review assesses the relationship between hospital nurses' work environment characteristics and patient safety outcomes and recommends directions for future research based on examination of the literature. Using an electronic search of five databases, 18 studies published in English between 1999 and 2016 were identified for review. All but one study used a cross-sectional design, and only four used a conceptual/theoretical framework to guide the research. No definition of work environment was provided in most studies. Differing variables and instruments were used to measure patient outcomes, and findings regarding the effects of work environment on patient outcomes were inconsistent. To clarify the relationship between nurses' work environment characteristics and patient safety outcomes, researchers should consider using a longitudinal study design, using a theoretical foundation, and providing clear operational definitions of concepts. Moreover, given the inconsistent findings of previous studies, they should choose their measurement methodologies with care.